ВИКОРИСТАННЯ МЕХАНІЗМІВ САМОРЕГУЛЮВАННЯ ПІД ЧАС ЕЛЕКТРОШЛАКОВОГО НАПЛАВЛЕННЯ У СТАЦІОНАРНОМУ СТРУМОПІДВІДНОМУ КРИСТАЛІЗАТОРІ - Соловйов, В.Г.; Романова, І.Ю. (Інститут електродинаміки НАН України, Київ, 2025)
In a situation where there is no automatic control system for electroslag melting in a stationary current-supplying mould using a consumable electrode, a method of mechanized melting with specified technological characteristics of the product has been proposed, utilizing self-regulation mechanisms. The method is based on mechanized melting, which involves the use of specialized equipment to automation control of the melting process, while a number of preparatory technological operations are performed manually. This method combines the advantages of automatic control with the flexibility of manual melting, which helps to increase the productivity and quality of the deposited layer. Partial automation involves mandatory automatic control of key technological parameters during melting, such as current, power, electrical conductivity, and voltage supplied to the stationary current-supplying mouldr. References 12, figures 6.